Synthesis and characterization of baco2 w-type hexaferrite with addition of carbon black - Azreen Shafirah, Abdullah (2025)
Electronic devices contribute to electromagnetic wave interference causing electromagnetic pollution that affects human health. Electromagnetic pollution was managed by the application of microwave absorber material by controlling reflection loss. The low absorption, narrow bandwidth, and impedance mismatch were related to the reflection loss. BaCo2Fe16O27 was doped with carbon black to increase the absorption, broaden bandwidth, and enhance impedance matching to improve the efficiency of absorption of the material. The BaCo2Fe16O27 was produced by the solid-state method using the ball milling technique at 300 rpm for 12 hours and sintered at 1250 ℃ for 5 hours. Carbon black (10%, 20%, 30%, and 40%) was doped with BaCo2Fe16O27 to fabricate composite material with thicknesses of 1 mm, 2 mm, and 3 mm. The structural, microstructural, and absorption performance was characterized using X-ray Diffraction, Scanning Electron Microscopy, and Vector Network Analyzer. The absorption performance was tested at frequencies ranging from 8 to 18 GHz. The structural analysis confirmed the single-phase formation of BaCo2Fe16O27 with an average crystallite size of 33.19 nm. The microstructural showed spongy and irregularly grain-shaped samples. The reflection loss value increases with the increase of the composition of carbon black improving electromagnetic wave absorption. By varying the thicknesses and composition of carbon black, the microwave absorber material achieved the effective value of reflection loss and frequency. The maximum reflection loss reached about -27.42 dB at a frequency of 9.24 GHz when the thickness was 3 mm on 40% of carbon black and was defined as an excellent absorber material.